نظرية المخاطر كأساس للمسؤولية الدولية عن أعمال مجلس الأمن المشروعة دولياً والمتسمة بخطورة استثنائية - Ali, Hadeel; NAeem, Hadi (Journal of Legal Sciences, 2022)
International responsibility rises against the United Nations Organization for the actions of the Security Council according to the theory of risks, in the event that ships, submarines and aircraft carriers that operate with nuclear energy are launched against countries that violate the provisions of Chapter VII the Charter of the United Nations, considering that the Council’s actions here are considered as internationally legitimate acts of exceptional risks that the Council may resort to it in order to ensure the speed and effectiveness referred to in Article (11 / Paragraph 2) of the charter and to keep pace with developments in modern technology.